Coherent THz Emission Enhanced by Coherent Synchrotron Radiation Wakefield - Di Mitri, S. (Sci Rep, 2018)
We demonstrate that emission of coherent transition radiation by a ∼1 GeV energy-electron beam passing through an Al foil is enhanced in intensity and extended in frequency spectral range, by the energy correlation established along the beam by coherent synchrotron radiation wakefield, in the presence of a proper electron optics in the beam delivery system. Analytical and numerical models, based on experimental electron beam parameters collected at the FERMI free electron laser (FEL), predict transition radiation with two intensity peaks at ∼0.3 THz and ∼1.5 THz, and extending up to 8.5 THz with intensity above 20 dB w.r.t. the main peak. Up to 80-µJ pulse energy integrated over the full bandwidth is expected at the source, and in agreement with experimental pulse energy measurements. By virtue of its implementation in an FEL beam dump line, this work promises dissemination of user-oriented multi-THz beamlines parasitic and self-synchronized to EUV and x-ray FELs.